Becoming-Black Bloc, Becoming-Anartist: the art of prolonging and remodulating counter-cultural lines of flight (FORUM: University of Edinburgh Postgraduate Journal of Culture & the Arts, 2018)
The text describes the practice of the Anartist, which consists of interventions that subvert the urban space with an antagonist and countercultural spin inspired by the Black Bloc. The evil aura and the symbolic violence of the Black Blocks, a sort of magical Black Mana, are folded into a subversive aesthetic expressiveness that opens a line of escape in the urban space and provokes a viral infection in the Integrated Spectacle of Capitalism. The Anartist, a masked transpersona that can be embodied by anybody, extends the counter-spectacle of the Black Bloc destructive actions in disruptive line of flights that actualize their telluric subversion in site-specific situations of the urban space. The Anartist is a sort of simulacrum that decentralizes, remodulates and intensifies the counter-cultural mythology of Black Blocks. The practice of the Anartist, which can be defined as Disturbanism, unworks the money-form of the space, unleashing an event that is out of capitalist design but which arises from within itself as a virus that causes a negative diarrhea of dissensus. In fact, the Anarchist Disturbanist intervention can be considered as the unappropriated other that cannot be expelled outside by a totalitarian system that has no outside and returns as a viral scatological hauntology. The Anartist produces chaos, symbols and experiences through Black shit, ghosts and antagonist viruses to operate witchcraft rituals, which not only cannot be subsumed by the Capitalist Spectacle but continue to infect it in an eternal return producing a counter-culture and a counter-spell.